An Investigation of Repurchase Intentions in the Banking Industry: What Reason Do They Return?. (January 2022) - Sohaib, Muhammad
In an increasingly competitive market, customer retention is imperative for businesses in the services sector, particularly banks. This study aims to understand how relationship quality as second-order impacts repurchase intentions based on the Theory of Repurchase Decision Making (TRD). The switching cost moderating role is addressed. The model was validated using empirical data from Pakistan. A regression modeling was adopted to measure the research hypotheses that underpinned a proposed conceptual model. Results show that relationship quality positively and significantly influences the repurchase intentions. Switching cost determined to be a moderator between relationship quality and repurchase intentions. The implication is that services industry professionals should not overlook the importance of relationship quality and switching costs, as they have a significant impact on repurchase intentions.